PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN PADA 9FEET POOL & CAFE DI SEMARANG - Putri Puspasari, 07.05.51.0117; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2013)
One of the challenges faced by humankind in the future is to create a more diverse organization but at the same time demand management more efficient, effective, and productive. This meant that the organizations dependence on human resource management is increasingly high quality will be greater. To realize such a situation, should increase awareness of the purpose of all human resource activities. The company or organization has a number of resources (resources), which are human resources. Because humans are a source of inspiration and driving force of the functions of the organization. Therefore, human resources should be maintained properly, because if it is not done, it will result in a reduction of resources caused by the release of potential human resources (turnover intention). The release of human resources from work can be caused by several things, such as job satisfaction and organizational commitment. Karyawanpun required to work more optimally, thus increasing employee productivity and company. However, in order to increase the productivity of labor, every employee should have the satisfaction in his work, so that employees have a commitment to the organization. This study aimed to examine the effect of job satisfaction commitment organisasiterhadap employee turnover intention 9feet pool & cafe in Semarang The object used is an employee 9Feet Pool & CafÃ© .. The samples in this study were all employees of 9 feet and pool, amounting to 35 respondents. Is the primary data type. Methods of data collection using questionnaires. The analysis technique used is multiple regression. SPSS Test results proved that the influence between job satisfaction and organizational commitment to employee turnover intention 9feet & poolkepuasan affect job turnover intention. value of r square of 0.608. This suggests that the ability of the variables job satisfaction and organizational commitment in influencing turnover intention is at 60.8% Key words: Job satisfaction, organizational commitment and Turnover Intention